Mild Anemia May Affect Thyroid Function in Pregnant Chinese Women During the First Trimester - Nie, Guan-ying; Wang, Rui; Liu, Peng; Li, Ming; Sun, Dian-jun (Frontiers in Endocrinology, 2021)
Background Pregnant women are often susceptible to anemia, which can damage the thyroid gland. However, compared with moderate and severe anemia, less attention has been paid to mild anemia. The purpose of this study was to evaluate the effect of mild anemia on the thyroid function in pregnant women during the first trimester. Methods A total of 1,761 women in the first trimester of their pregnancy were enrolled from Shenyang, China, and divided into mild anemia and normal control groups based on their hemoglobin levels. Thyroid-stimulating hormone (TSH), free thyroxine (FT4), and free triiodothyronine (FT3) levels were compared between the two groups. Results The TSH levels of pregnant women with mild anemia were higher than those of pregnant women without mild anemia (p < 0.05). Normal control women were selected to set new reference intervals for TSH, FT3, and FT4 levels during the first trimester, which were 0.11–4.13 mIU/l, 3.45–5.47 pmol/l, and 7.96–16.54 pmol/l, respectively. The upper limit of TSH 4.13 mU/l is close to the upper limit 4.0 mU/l recommended in the 2017 American Thyroid Association (ATA) guidelines, indicating that exclusion of mild anemia may reduce the difference in reference values from different regions. Mild anemia was related to 4.40 times odds of abnormally TSH levels (95% CI: 2.84, 6.76) and 5.87 increased odds of abnormal FT3 (95% CI: 3.89, 8.85). The proportion of hypothyroidism and subclinical hypothyroidism in patients with mild anemia was higher than that in those without anemia (0.6% vs. 0, p = 0.009; 12.1% vs. 1.9%, p < 0.001). Mild anemia was related to 7.61 times increased odds of subclinical hypothyroidism (95% CI: 4.53, 12.90). Conclusions Mild anemia may affect thyroid function during the first trimester, which highlights the importance of excluding mild anemia confounding when establishing a locally derived specific reference interval for early pregnancy.